2012
DOI: 10.1002/ijc.27403
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated macrophages correlate with response to epidermal growth factor receptor‐tyrosine kinase inhibitors in advanced non‐small cell lung cancer

Abstract: Our study investigated whether tumor-associated macrophages (TAMs) in advanced non-small cell lung cancer (NSCLC) are related to treatment response to epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) and may be a predictor of survival. Of 206 advanced NSCLC patients treated (first-line) with an EGFR-TKI at the study hospital from 2006 to 2009, 107 with adequate specimens for assessing CD68 immunohistochemistry as a marker of TAMs were assessed. After EGFR-TKI treatment, response was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 33 publications
8
70
0
Order By: Relevance
“…Our results showed that the expression of CD163 was significantly increased in all NSCLC subtypes (adenocarcinoma, squamous cell lung carcinoma and large cell lung carcinoma) compared to nontumour tissues. A study that investigated TAMs in advanced NSCLC found that more than 95 % of CD68 + TAMs were located in the tumour stroma and were positively co-stained with CD163 [33]. Also, the CD68 + and CD163 + TAMs count was found to be significantly increased in patients with progressive disease [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the expression of CD163 was significantly increased in all NSCLC subtypes (adenocarcinoma, squamous cell lung carcinoma and large cell lung carcinoma) compared to nontumour tissues. A study that investigated TAMs in advanced NSCLC found that more than 95 % of CD68 + TAMs were located in the tumour stroma and were positively co-stained with CD163 [33]. Also, the CD68 + and CD163 + TAMs count was found to be significantly increased in patients with progressive disease [33].…”
Section: Discussionmentioning
confidence: 99%
“…A study that investigated TAMs in advanced NSCLC found that more than 95 % of CD68 + TAMs were located in the tumour stroma and were positively co-stained with CD163 [33]. Also, the CD68 + and CD163 + TAMs count was found to be significantly increased in patients with progressive disease [33]. Furthermore, other studies have shown that the expression of the M2 marker in TAMs was significantly correlated to poor prognosis, p-TNM staging and lymph node metastasis in patients with advanced adenocarcinoma [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…37 The site of TAM infiltration also influences prognosis. Multiple reports found increased stromal TAM density to be independent predictor of reduced survival, whereas TAM density in tumor islets correlated with a good prognosis.…”
Section: Lung Cancermentioning
confidence: 99%
“…37 Patients with progressive disease had significantly higher TAM counts, and high TAM counts were significantly related to poor progression-free survival (PFS) and OS. 37 Studies using CD204 as an M2 marker indicated a significant association of CD204 + TAM density and poor outcome of patients with adenocarcinoma 41 and squamous cell carcinoma of the lung. 42 As an interesting finding, the number of circulating CD14 + CD204 + cells in the pulmonary vein of NSCLC patients correlated with the number of CD204 + TAMs in the tumor stroma and was a significant independent risk factor for early recurrence.…”
Section: Lung Cancermentioning
confidence: 99%
“…Because of the continuous contact of airway lung epithelial cells with invading microbes, the pulmonary microenvironment represents a unique milieu in which carcinogenesis can proceed supported by an inflammatory context and by the presence of a significant population of immunosuppressive cells. TAMs are one of the major immunosuppressive cells affecting the tumor microenvironment able to influence tumor progression and the success or failure of immunotherapy, 26 and emerging evidence reveals a significant correlation between high TAM numbers and poor patient prognoses in lung cancer patients.In advanced NSCLC patients treated (first-line) with an EGFR-TKI, M2-polarized counts was associated with a marked decrease in treatment response 27 and correlated with lymph node metastasis and poor prognosis. 28,29 Moreover, several studies have suggested a role for the expression of the immunosuppressive cytokine IL-10 by TAMs in the progression and prognosis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%